(untitled) (Baghdad Science Journal, 2013)
Starting from bis (4,4’-diamino phenoxy) ethan(1), a variety of phenolicschiff bases (methylolic, etheric, epoxy) derivatives have been synthesized. All proposed structure were supported by FTIR, 1H-NMR, 13C-NMR Elemental analysis, some derivatives evaluated by thermal analysis (TGA).